Strategi bersaing live streaming Tiktok dengan pendekatan SOAR dan Porter Five Forces pada Brand Kuliterian - Silvia, Mega; Shiddied, Diqy Fahrun; Roji, Fikri Fahru (Nur Science Institute, 2025)
Kuliterian is one of the leather fashion industry players that is facing stiff competition in utilizing TikTok live streaming as a marketing strategy. The development of digital technology and the increase in TikTok users provides new opportunities and challenges for Kuliterian in attracting and retaining an audience, as well as competing with other, more established brands. The main objective of this research is to develop a competitive strategy based on live streaming on TikTok to increase Kuliterian’s competitiveness. This research uses a qualitative descriptive method with a SOAR and Porter’s Five Forces analysis approach. The research results show that Kuliterian needs to optimize content creativity, collaborate with influencers, and utilize TikTok analytical data to increase interaction with consumers. The resulting strategy includes product differentiation, technological innovation, loyalty program development, and brand strengthening. By integrating strategies based on internal potential and competitive analysis, this research provides new insight for Kuliterian in maximizing the potential of TikTok live streaming to increase its competitiveness in the digital fashion market.